Land-use and land-cover changes and emerging non-tuberculous and tuberculous infectious diseases in humans and animals: a mixed-methods review of research findings from global and spatio-temporal perspectives - Jean-François Guégan; Carlos A Vargas Campos; Christine Chevillon; Ahmadou Sylla; Magdalene Dogbe; Kayla M Fast; Jennifer Pechal; Alex Rakestraw; Matthew E Scott; Michael W Sandel; Heather Jordan; M Eric Benbow (Environmental Research: Health)
Despite recent interest in land-use and land-cover (LULC) change effects on emerging infectious diseases (EIDs), the debate on global potential health threats remains polarizing. These depend on diverse LULC changes, different types of infectious disease systems, and spatio-temporal scales of studies. Here, using both a bibliometric and scoping review method, we summarize the reliability and availability of published relevant studies on LULC effects on mycobacteria, an important group of infectious bacteria that affect humans and both wild and domestic animals. We make connections of LULC with environmental changes (e.g. soils) that likely lead to an increased risk of mycobacteria spillover to human and other animal populations. An important feature of our review is a focus on research from the richest countries of the world, though some studies have been done in Africa, Asia and South America. Geographically, regions experiencing important LULC transformations, such as many tropical regions of Meso- and South America and Southeast Asia, have been given little or no attention in this important topic. Research on Mycobacterium bovis, and to a larger extent on M. ulcerans, constitutes convincing illustrations of the importance of acknowledging shifts in spatio-temporal scales, from local to global and inter-annual to decadal ones, when evaluating responses of mycobacteria to LULC changes. However, studies on other pathogenic mycobacteria remain very much confined to local and dispersed scales. To date, the role of LULC change effects has not been adequately studied for many human and animal pathogens, and more research and attention to this issue is clearly needed. This review provides a comprehensive set of data on the updates of LULC change and their impact on animal and human mycobacterial infections. It also proposes several research recommendations, in particular to better understand the emergence of mycobacteria in context, by multiplying study sites in different regions of the world and in adopting an ecosystem-based perspective, in order to encourage interdisciplinary research better linking environmental microbiology, veterinary science and medical research.